ESTIMATING CANOPY HEIGHT AND WOOD VOLUME OF EUCALYPTUS PLANTATIONS IN BRAZIL USING GEDI LIDAR DATA - Fayad, Ibrahim (2021)
Full waveform (FW) LiDAR systems have gained momentum to map forest biophysical variables in the last two decades, owing to their ability to accurately estimate canopy heights and aboveground biomass. Currently, the Global Ecosystem Dynamics Investigation (GEDI) system on board of the International Space Station (ISS) is the most recent FW spaceborne LiDAR instrument for the continuous observation of earth's forests. Here, we assess the accuracy of GEDI FW data for the estimation of stand-scale dominant heights (Hdom), and stand volume (V) using linear and nonlinear regression models based on several GEDI metrics. The models were calibrated and validated using in-situ data from Eucalyptus plantations in Brazil. Overall, the most accurate estimates of Hdom and V were obtained using the stepwise regression, with an RMSE of 1.44 m (R2 of 0.92) and 24.39 m3.ha-1 (R2 of 0.90) respectively. The principal metric explaining more than 87% and 84% of the variability (R2) of Hdom and V was the metric representing the height above the ground at which 90% of the waveform energy occurs.